Lima Kepribadian Tokoh Karang dalam Novel Rintik Terakhir Karya Sri Puji Hartini - Irdiansyah, Nabilla Putri; Ahmadi, Anas (UPA Bahasa Universitas Tidar And HISKI Kedu, 2024)
This research uses the novel entitled Last Rintik by Sri Puji Hartini as the main data to be studied and analyzed. Because the main character named Karang has a psychological disorder in the form of Dissociative Identity Disorder (DID) or commonly known as multiple personality. A person who experiences multiple personalities has an abnormal psychological condition due to trauma in the past. This causes Karang to have 4 other personalities within himself. Karang's personalities can be analyzed using Sigmund Freud's personality theory. The method used in this research is a qualitative method with a descriptive approach. The results of this research show that Karang's personalities can be analyzed using Sigmund Freud's personality theory. It can be concluded that every personality in Karang's body has the three personality structures of ideas, ego and superego in Sigmund Freud's personality theory.